Civil control over the activity of the subjects of public administration - Маслова, Яна Іванівна; Маслова, Я. І.; Маслова, Яна Ивановна; Maslova, Yana I.; Савчук, Роман Михайлович; Савчук, Р. М.; Savchuk, Roman M. (Riga : Izdevniecība “Baltija Publishing”, 2020)
The article is devoted to the study of the theoretical and legal foundations of civil control over the activities of public administration. There are such specific features that are inherent in civil control, as: the subject of civil control are citizens and public associations that are organizationally and functionally independent of the objects of control; the object of civil control is the sphere of public administration; the purpose of civil control is to ensure the public interest; civil control is exercised exclusively in the manner prescribed by law; provided by moral and legal measures of influence; the results of civil control may be the basis for other types of civil control provided by state coercion. The basic principles of functioning of the institute of citizens’ appeals as a form of civil control over the activity of public administration subjects are analyzed.

Стаття присвячена дослідженню теоретико-правових основ цивільного контролю за діяльністю органів державного управління. Виділяють такі специфічні ознаки, які притаманні цивільному контролю, як: суб’єктом цивільного контролю є громадяни та громадські об’єднання, організаційно та функціонально незалежні від об’єктів контролю; об'єктом цивільного контролю є сфера державного управління; метою цивільного контролю є забезпечення суспільних інтересів; цивільний контроль здійснюється виключно у встановленому законом порядку; передбачені морально-правовими заходами впливу; результати цивільного контролю можуть бути підставою для інших видів цивільного контролю, передбачених державним примусом. Проаналізовано основні принципи функціонування інституту звернень громадян як форми цивільного контролю за діяльністю суб’єктів державного управління.
Maslova Ya. I. Civil control over the activity of the subjects of public administration / Ya. I. Maslova, R. M. Savchuk // Public administration under modern conditions: concept, features, challenges : Collective monograph. - Riga : Izdevniecība “Baltija Publishing”, 2020. - P. 99-113.
Keywords: civil control; public administration; institute of citizens’ appeals; цивільний контроль; державне управління; інститут звернень громадян; Research Subject Categories::LAW/JURISPRUDENCE::Public law